Optical fiber sensor for monitoring the strain of concrete which subject to freezing and thawing test - Liao, Kaixing; Lv, Haifeng; Kong, Xianglong; Sun, Changsen; Zhao, Xuefeng (SPIE, 2018)
In order to monitor the strain of concrete which caused by freeze-thaw (F-T) cycles, a novel type of white light interferometer (WLI) sensor is designed and tested. The single-mode optical fiber is embedded in the cement mortar ring as strain gauge, after that, poured the cement mortar ring into concrete cylinder. To study the feasibility of the proposed measurement, two concrete cylinders are exposed in a temperature chamber which uses to simulate the F-T environment. The strain is monitored at 15°C after every 10 cycles. Temperature compensation method is conducted to eliminate the optical fiber strain which caused by temperature. The results indicate that the monitoring method is stable and the residual strain increases with F-T cycles